Research on the Mechanism of Cold Chain Logistics Subsidy - Nai-Ru Xu; Zheng-Qun Cai (Journal of Chemistry)
Considering the coexistence of cold chain agro-products and ordinary agro-products in the market, the research object is the cold chain logistics subsidy. It is designed that a supply chain system consisting of duopoly upstream agro-products suppliers and a downstream agro-products retailer for research. The mechanism of cold chain logistics subsidy is studied by analyzing the influence of cold chain subsidy on pricing behavior and cold chain decision-making of cold chain agro-products and ordinary agro-products. Based on the decentralized decision-making model without government subsidy, a differential pricing model for cold chain agro-products and ordinary agro-products with government subsidy is established in order to reduce the cost of cold chain agro-products. The optimal pricing strategy of two agro-products suppliers and their downstream retailer can be obtained by solving this problem. The research finds that differential pricing caused by government subsidy can achieve profit Pareto improvement of suppliers, retailer, and supply chain system of cold chain agro-products, but cannot achieve the optimal profit of the whole supply chain. Therefore, in view of the loss of supply chain efficiency caused by decentralized decision-making, the Shapley value method is used to make coordination, and the contract coordination mechanism is designed. Finally, the sensitivity of parameters is analyzed by a numerical example.